Perceived Training Preferences Of Livestock Farmers In Karnataka - Balaraju, B.L.; Khandekar, Prakash; Chander, Mahesh; Rathod , Prakashkumar; Pachiayappan , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An ex-post-facto exploratory study was conducted using 120 livestock farmers to collect data about the preferred type, venue, method, season, duration, interval and timings of the training in Davangere district of Karnataka on three point continuum viz., most preferred, preferred and least preferred. Majority of livestock farmers preferred one day to less than one week training duration preferably in the evening hours of winter season at their own village in the form of farm visits and demonstrations with one year time interval between successive trainings. Hence, livestock extension agencies have to organize trainings according to farmers’ preference for effectiveness of training and increase in livestock productivity.